KEKUATAN E-MAIL SEBAGAI ALAT BUKTI DALAM PROSES PERSIDANGAN PERKARA PERDATA DI INDONESIA - Mery Maryati (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTThe study is titled “THE POWER OF E-MAIL AS A TOOL OF EVIDENCE IN CIVIL JURISDICTION PROCESS IN INDONESIA” The problem will be discussed in scholarly works is how the power of email as evidence in civil case trials in Indonesia. The methods used in the writing of scientific papers this is normative legal research methods. The strength of e-mail as a process of evidence in court if it is related to article 1866 of the Civil Code regarding valid evidence, then the strength of e-mail when printed is considered the same as the original letter and has the same strength as an authentic deed. The main requirement so that a document electronic or electronic mail (e-mail) can be declared evidence is validating it must include an electronic signature in the electronic document or electronic mail (e-mail) (articles 5-12 of the ITE Law), and In using the electronic system, the electronic certification has been obtained from the government or related parties (articles 13-16 of the ITE Law).  The Thusposition of an electronic document is actually a evidence valid  and together with written evidence. The power of proof of written documents in civil case proof very much depends on the form and purpose of the document being made, electronic documents can be referred to as authentic deeds if they have received certification from the government or related parties and meet other requirements as a valid electronic contract. However, if the electronic system and electronic documents used have not received certification, then every document that has been made will still be considered invalid by law.Keywords: E-mail, Evidence, Trial.